Recurrence risk after a first remote symptomatic seizure in adults: Epilepsy or not? - Johan Zelano (Wiley, 2021)
Abstract The ILAE practical definition of epilepsy has a one seizure possibility to diagnose epilepsy after a first seizure if the recurrence risk is very high. The recurrence risk after a first seizure in brain disorders (first remote seizure) is often high, but varies with etiology, so more specific information is needed for clinical practice. This review describes etiology‐specific recurrence risks in adults with a first remote seizure in stroke, traumatic brain injury, infections, dementia, multiple sclerosis, and tumors. Most studies are short, single center, and retrospective. Inclusion criteria, outcome ascertainment, and results vary. Few patient categories are clearly above the epilepsy threshold of recurrence risk, and there are surprisingly little data for important etiologies like brain infections. Beside stroke, severe TBI could have a sufficiently high recurrence risk for early epilepsy diagnosis, but more studies are needed, preferably prospective ones. The literature is uninformative regarding which seizures qualify as remote. The clinical implication of the low level of available evidence is that for other etiologies than stroke, seizure recurrence remains the most appropriate indicator of epilepsy for most patients with a first remote seizure. Nonetheless, there are worrying indications of a diagnostic drift, which puts patients with a preexisting brain disorder at risk of misdiagnosis. Although there are drawbacks to an intermediate term like “possible epilepsy,” it could perhaps be useful in cases when the recurrence risk is high, but epilepsy criteria are not definitely met after a first remote seizure.